MANAJEMEN STRESS KERJA PADA KARYAWAN PERUSAHAAN - Nurma Aini Harahap; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The comfort factor for employees is something that must be considered by the company so that employees feel at home working in the company so that employees will become loyal, thus their performance will be better. The design of this research is literature review or literature review. Stress management is included in human resources in the maintenance section. Maintenance is an effort to maintain and or improve the physical, mental, and attitude of employees so that they remain loyal and work productively to support the achievement of company goals. This stress management depends on how the company handles the stress experienced by employees. Each work stress program first knows whether there is stress and the causes of the stress, so that management can determine what actions or work stress management are effective. Stress Management for Employees has many benefits, namely minimizing sick days, strong corporate culture, creating stress management programs for employees, identifying causes of stress, building a culture of reward and recognition, and focusing on employee health